KAJIAN PERUBAHAN RUANG DAN SOUNDMARK KAWASAN WISATA PUSAKA TAMANSARI YOGYAKARTA - Patricia Pahlevi Noviandri; Ferdy Sabono (ATRIUM: Jurnal Arsitektur, 2018)
Title: Study of Space Changing and Soundmark in Tamansari Heritage Tourism Area, Yogyakarta Tamansari area is an area of historical value. Until now, this region has been conserved and used as a heritage tourism. The Tamansari site, which has not been used anymore since the reign of Sultan Hamengkubuwono III, has caused the growth of residential areas around it. This causes a change in the solid void of the Tamansari area. Changes in the existing building structure create differences in the soundscape of the area that was once the location of the palace retreat and is now a heritage tourism area. In this study will discuss the changes that occur in the mass management of buildings in the Tamansari area that will affect the environmental acoustics of the area. This research method uses qualitative deductive method by comparing the shape of the space during the active period of the building as the resting of the Keraton family with the current building mass discussed with the theory of space and acoustic environment. The results of this study are changes in ground figures and linkages showing changes in the soundmark of the Tamansari area. Changing ground figures make the impact of increasingly diverse activities appear. Soundmark changed from the dominant calm voice to the nois dominant. The soundmark area changes from sounds that support a sacred atmosphere with sounds that are due to building density. This change in soundmark creates a change of sense of place from the Tamansari area.